Assessment of Nitrogen Ceilings for Dutch Agricultural Soils to Avoid Adverse Environmental Impacts - Wim de Vries; Hans Kros; Oene Oenema; Jan Willem Erisman (The Scientific World Journal)
In the Netherlands, high traffic density and intensive animal husbandry have led to high emissions of reactive nitrogen (N) into the environment. This leads to a series of environmental impacts, including: (1) nitrate (NO3) contamination of drinking water, (2) eutrophication of freshwater lakes, (3) acidification and biodiversity impacts on terrestrial ecosystems, (4) ozone and particle formation affecting human health, and (5) global climate change induced by emissions of N2O. Measures to control reactive N emissions were, up to now, directed towards those different environmental themes. Here we summarize the results of a study to analyse the agricultural N problem in the Netherlands in an integrated way, which means that all relevant aspects are taken into account simultaneously. A simple N balance model was developed, representing all crucial processes in the N chain, to calculate acceptable N inputs to the farm (so-called N ceiling) and to the soil surface (application in the field) by feed concentrates, organic manure, fertiliser, deposition, and N fixation. The N ceilings were calculated on the basis of critical limits for NO3 concentrations in groundwater, N concentrations in surface water, and ammonia (NH3) emission targets related to the protection of biodiversity of natural areas. Results show that in most parts of the Netherlands, except the western and the northern part, the N ceilings are limited by NH3 emissions, which are derived from critical N loads for nature areas, rather than limits for both ground- and surface water. On the national scale, the N ceiling ranges between 372 and 858 kton year–1 depending on the choice of critical limits. The current N import is 848 kton year–1. A decrease of nearly 60% is needed to reach the ceilings that are necessary to protect the environment against all adverse impacts of N pollution from agriculture.